In Vivo Effects of Nanotechnologically Synthesized and Characterized Fluoridated Strontium Apatite Nanoparticles in the Surgical Treatment of Endodontic Bone Lesions - Oztekin, Faruk; Gurgenc, Turan; Dundar, Serkan; Ozercan, Ibrahim Hanifi; Eskibaglar, Mehmet; Ozcan, Erhan Cahit; Habek, Osman (Mdpi, 2022)
In this study, fluoridated strontium apatite (SAP) nanoparticles with different mole percentages (5%, 10%, 30%, and 50%) synthesized using a hydrothermal method were used as biomaterials. The in vivo biocompatibility of the synthesized nanoparticles was investigated by embedding them as biomaterials in bone defects created in rat tibiae. Through the hematoxylin-eosin staining method, a histopathological analysis was performed for new bone formation, osteoblast density, and fibrotic tissue formation. Fluorine (F) addition affected the structural and morphological properties of the nanoparticles. With the F doping, the shapes of the nanoparticles changed from nano-rods to almost spherical. The Sr/P ratios, with a stoichiometric value of 1.67, were 1.76, 1.53, 1.54, 1.68, and 1.79 in pure, 5%, 10%, 30%, and 50% F-doped nanoparticles, respectively. The F/Sr ratios of 5%, 10%, 30%, and 50% F-doped nanoparticles were 0.05, 0.13, 0.16, and 0.20, respectively. The highest values in terms of fibrotic tissue formation were obtained in the group containing pure SAP. The best results in terms of new bone formation and osteoblast density in bone defects were observed in the groups with higher F ratios (30% and 50% F-doped). Pure and F-doped strontium apatite nanoparticles showed good results for new bone formation and osteoblast levels compared to the control group. It was observed that an increase in the fluorine ratio resulted in better bone healing. The results showed that pure and F-doped SAP nanoparticles synthesized by a hydrothermal method can be used as biomaterials in orthopedics and dentistry, especially in the surgical treatment of endodontic lesions.
Keywords: endodontic lesions; strontium apatite; fluorine; osteoblasts; new bone formation